Comparative analysis of demographic dynamics in the context of human development in Bashkortostan and Tatarstan (1959–2021) - Valiakhmetov, Rim M.; Lomanova, Aleksandra K.; Abylkalikov, Salavat I. (The New Research of Tuva, 2024)
The article presents a comparative analysis of demographic processes in the Republic of Bashkortostan and the Republic of Tatarstan — two regions of Russia. These republics have similar historical and cultural features as well as socio-economic development levels, but they exhibit contrasting demographic trends. While Tatarstan demonstrates steady population growth, partly driven by migration flows, Bashkortostan experiences demographic stagnation.The analysis focuses on differences in birth rates, mortality rates, and migration patterns in both urban and rural areas, using data from population censuses and statistics provided by official statistics of Russia from 1959 to 2021. Emphasis is placed on the interrelation between these demographic processes and human capital development.The results of the study show that Tatarstan's more dynamic economic growth, advanced urban infrastructure, and higher investment in human development contribute to its migration attractiveness and, consequently, its population growth trends. In contrast, Bashkortostan exhibits less favorable socio-economic conditions and a lower level of human capital development. These factors lead to population outflows from the region and demographic stagnation.The authors also examine the mutual influence of demographic changes and human capital development, highlighting the need to devise region-specific demographic policies aimed at sustaining human capital and ensuring demographic stability. The article addresses issues of socio-economic development and institutional factors influencing demographic and migration behavior as well as human capital development in the regions.
Keywords: demography; migration; Bashkortostan; Tatarstan; population dynamics; demographic balance; human capital; population census; birth rate; mortality rate